The Effect Of The Scramble Learning Model On The Critical Thinking Abilities Of Grade 2 Students In The Science Subject At Donggobolo Elementary School - selvitriana, Ayu; Suryaningsi, Sri; Atmaja, Jessy Parmawati (Lembaga Penelitian dan Pendidikan Mandala, 2026)
The background of this research stems from the importance of mastering critical thinking skills from an early age in elementary school, especially in facing the rapid development of science and technology. The purpose of this study was to determine the effect of the Scramble learning model on the critical thinking abilities of second-grade students in the IPAS subject at SDN Donggobolo. This research employed a quantitative approach using a quasi-experimental design in the form of a nonequivalent control group design. The research subjects consisted of all second-grade students at SDN Donggobolo, totaling 33 students, comprising 16 students in the experimental class and 17 students in the control class. The instrument used was an essay test designed to measure students’ critical thinking skills. The data analysis technique was carried out through several stages, namely prerequisite tests including normality and homogeneity tests, followed by hypothesis testing using an independent sample t-test. The results of the analysis indicated that the significance value (2-tailed) was 0.001 < 0.05, thus rejecting the null hypothesis (Ho) and accepting the alternative hypothesis (Ha). Therefore, it can be concluded that the use of the Scramble learning model has a significant effect on improving the critical thinking skills of second-grade students. These findings suggest that the implementation of the Scramble learning model can serve as an innovative instructional strategy to enhance the quality of the teaching and learning process, particularly in IPAS learning at the elementary school level.